Biologics in severe uncontrolled chronic rhinosinusitis with nasal polyps: A bicentric experience - Bellocchi, Gianluca; Loperfido, Antonella; Passali, Francesco Maria; Millarelli, Stefano; Velletrani, Gianluca; Perla, Marco; Di Michele, Loreta; Di Girolamo, Stefano (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: The introduction of biologics in the management of chronic rhinosinusitis with nasal polyposis (CRSwNP) has allowed new therapeutic options and Dupilumab represents the first approved biological agent. Aim of this paper is to provide a multicentric study in a real-life setting of treatment with Dupilumab for severe uncontrolled CRSwNP in Italy. Methods: A retrospective data collection was performed from the departments of Otolaryngology of two major health institutions in Rome: San Camillo Forlanini Hospital and Tor Vergata University. Both centres contributed to the study providing information about patients affected by severe uncontrolled CRSwNP and treated with Dupilumab. Results: A total of 83 patients were included in the study (43 males; 40 females; mean age: 55.8 years). Monitoring our patients, we observed improvement in reduction of nasal polyposis and nasal obstruction, respectively measured through NPS and PNIF. Concerning the CRSwNP symptoms and their impact on quality of life, we found an improvement in the olfaction, as measured respectively by SSIT-16 and SNOT-22. Conclusions: Dupilumab has demonstrated broad efficacy in CRSwNP management. Further studies are needed to confirm our results and to establish biomarkers to identify endotypes and predict response to biologics treatment in CRSwNP.